The Wnt regulator SFRP4 inhibits mesothelioma cell proliferation, migration, and antagonizes Wnt3a via its netrin-like domain - Perumal, Vanathi; Dharmarajan, Arunasalam; Fox, Simon (Spandidos Publications, 2017)
Secreted frizzled related proteins (SFRPs) are a family of Wnt regulators which are frequently downregulated in cancers. In malignant mesothelioma (MM), downregulation of SFRP4 has been reported as a mechanism which contributes to aberrant activation of oncogenic Wnt signaling. Here we investigated the biological consequences of SFRP4 in two mesothelioma cell models where this protein is downregulated. We used recombinant SFRP4 and transient overexpression to study changes in proliferation, migration and downstream signaling. We found that recombinant SFRP4 inhibited both proliferation and migration of MM cells as well as abrogating the stimulatory effect of recombinant Wnt3a. Morphologically SFRP4 induced a cytotoxic effect distinct from apoptosis and consistent with mitotic catastrophe. Overexpression of SFRP4 in these cell lines displayed similar effects as endogenous protein on cell viability, migration and nuclear morphology. We also used expression constructs to examine the role of the SFRP4 cysteine rich domain (CRD) and a netrin-like domain (NLD) in these effects. Interestingly, we found it was the NLD which mediated the biological effects of SFRP4 in these cells. Our results indicate that SFRP4 inhibits mesothelioma proliferation, migration and activates alternative cell death pathways. The finding that the NLD is responsible for these has broader implications for this protein family. Overall this study suggests that the Wnt pathway may prove a promising target for therapy in mesothelioma.